Advances in Visual Computing 6th International Symposium, ISVC 2010, Las Vegas, NV, USA, November 29 - December 1, 2010, Proceedings, Part III - Bebis, George; Boyle, Richard; Parvin, Bahram; Koracin, Darko; Chung, Ronald; Hammound, Riad.; Hussain, Muhammad; Kar-Han, Tan.; Crawfis, Roger; Thalmann, Daniel; Kao, David; Avila, Lisa.; et al. (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The three volume set LNCS 6453, LNCS 6454, and LNCS 6455 constitutes the refereed proceedings of the 6th International Symposium on Visual Computing, ISVC 2010, held in Las Vegas, NV, USA, in November/December 2010. The 93 revised full papers and 73 poster papers presented together with 44 full and 6 poster papers of 7 special tracks were carefully reviewed and selected from more than 300 submissions. The papers of part I (LNCS 6453) are organized in computational bioimaging, computer graphics, behavior detection and modeling, low-level color image processing, feature extraction and matching, visualization, motion and tracking, unconstrained biometrics: advances and trends, 3D mapping, modeling and surface reconstruction, and virtual reality. Part II (LNCS 6454) comprises topics such as calibration, pose estimation, and reconstruction, segmentation, stereo, registration, medical imaging, low cost virtual reality: expanding horizons, best practices in teaching visual computing, applications, and video analysis and event recognition. Part III (LNCS 6455) mainly contains papers of the poster session and concludes with contributions addressing visualization, as well as motion and tracking.
Poster Session -- Lunar Image Classification for Terrain Detection -- Surface Modeling of the Corpus Callosum from MRI Scans -- Track Detection for Autonomous Trains -- Local Descriptors for Document Layout Analysis -- CT Image Segmentation Using Structural Analysis -- Phase Space for Face Pose Estimation -- Contour Based Shape Retrieval -- Illumination Normalization for Robust Face Recognition Using Discrete Wavelet Transform -- Feature-Based Lung Nodule Classification -- Multiple-object Tracking in Cluttered and Crowded Public Spaces -- Compliant Interframe Coding for Motion-JPEG2000 -- EVP-Based Multiple-View Triangulation -- An Improved Shape Matching Algorithm for Deformable Objects Using a Global Image Feature -- Multi-scale Topo-morphometric Opening of Arteries and Veins: An Evaluative Study via Pulmonary CT Imaging -- Video Event Detection as Matching of Spatiotemporal Projection -- PixelLaser: Computing Range from Monocular Texture -- A Spatio-Spectral Algorithm for Robust and Scalable Object Tracking in Videos -- Driving Fatigue Detection Using Active Shape Models -- Outlier Removal in Stereo Reconstruction of Orbital Images -- Random Sampling Nonlinear Optimization for Camera Self-calibration with Modeling of Intrinsic Parameter Space -- Facial Fraud Discrimination Using Detection and Classification -- Segmentation of Abdominal Organs Incorporating Prior Knowledge in Small Animal CT -- Method of Interest Points Characterization Based C-HOG Local Descriptor -- Stereo-Based Object Segmentation Combining Spatio-Temporal Information -- Fast Motion Estimation Based on Search Range Adjustment Using Neighboring MVDs -- Towards Computational Understanding of Skill Levels in Simulation-Based Surgical Training via Automatic Video Analysis -- Biomedical Image Retrieval in a Fuzzy Feature Space with Affine Region Detection and Vector Quantization of a Scale-Invariant Descriptor -- Model Distribution Dependant Complexity Estimation on Textures -- Integrating Multiple Uncalibrated Views for Human 3D Pose Estimation -- A Novel Histogram-Based Feature Representation and Its Application in Sport Players Classification -- Facial Expression Recognition Using Facial Features and Manifold Learning -- Blurring Mean-Shift with a Restricted Data-Set Modification for Applications in Image Processing -- Detecting Straight Line Segments Using a Triangular Neighborhood -- Size Distribution Estimation of Stone Fragments via Digital Image Processing -- Image Enhancement by Median Filters in Algebraic Reconstruction Methods: An Experimental Study -- 3D Curvature-Based Shape Descriptors for Face Segmentation: An Anatomical-Based Analysis -- Computational Hemodynamics in Intracranial Vessels Reconstructed from Biplane Angiograms -- Object Distance Estimation Based on Stereo Vision and Color Segmentation with Region Matching -- Multiscale Information Fusion by Graph Cut through Convex Optimization -- A Fast Level Set-Like Algorithm for Region-Based Active Contours -- A Novel Hardware Architecture for Rapid Object Detection Based on Adaboost Algorithm -- Using Perceptual Color Contrast for Color Image Processing -- GPU Acceleration of Robust Point Matching -- A Wavelet-Based Face Recognition System Using Partial Information -- A Study of Hierarchical Correlation Clustering for Scientific Volume Data -- Subversion Statistics Sifter -- A Lossy/Lossless Coding Algorithm Using Histogram -- Stereo Matching in Mean Shift Attractor Space -- Undecimated Wavelet Transform-Based Image Interpolation -- The Influence of Multimodal 3D Visualizations on Learning Acquisition -- Visualizing Gene Co-expression as Google Maps -- A New Approach for Lighting Effect Rendering -- SemaTime - Timeline Visualization of Time-Dependent Relations and Semantics -- Comics Stylizations of 3D Scenes Using GPU -- Discovering Novelty in Gene Data: From Sequential Patterns to Visualization -- A Differential-Geometrical Framework for Color Image Quality Measures -- Three Dimensional Reconstruction Using Vertical Constraints from a Photograph -- A Framework for Visual and Haptic Collaboration in Shared Virtual Spaces -- Design and Costs Estimation of Electrical Substations Based on Three-Dimensional Building Blocks -- Generating Shaded Image with Lighting Using Image Fusion Space -- Automatic Detection of Morphologically Distinct Objects in Biomedical Images Using Second Generation Wavelets and Multiple Marked Point Process -- Imaging-Based Computation of the Dynamics of Pelvic Floor Deformation and Strain Visualization Analysis -- Exploiting Multiple Cameras for Environmental Pathlets -- On Supervised Human Activity Analysis for Structured Environments -- Human Behavior Analysis at a Point of Sale.
Keywords: Computer science; Computer vision; Computer graphics; Optical pattern recognition; Bioinformatics; Computer Science; Pattern Recognition; Computational Biology/Bioinformatics.; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; User Interfaces and Human Computer Interaction